Territorialités d'un parti politique en ville - L'exemple du Frelimo à Maputo, capitale du Mozambique/Territoriality of a political party in town - The example of Frelimo in Maputo, capital of Mozambique - (:unkn) unknown (My University, 2012)
This article highlights the role of the dominant political party (Frelimo) in urban governance in Maputo. Based on a study of local politics and local political practices, this paper analyzes how a number of precepts related to "good governance" are appropriate on the ground and locally transformed. In Mozambique, as in many other African countries, decentralization and democratization started in the early 1990s. The decentralisation process crystallizes the debate on the reconfiguration of political power and their relationship to the state. In 1992, the end of the civil war opened a new political era. The one-party rule, led by Frelimo, gives way to a democratic governance, characterized by multiparty and decentralization. However, in Maputo, the forms of territoriality developed by local authorities provide information on how reforms imposed by international donors are adapted by the Frelimo Party. They reveal the permanence of policy frameworks and practices inherited from the authoritarian socialist era.
Keywords: African Research